Robust model for the assignment of outgoing flights on airport baggage unloading areas. (July 2018) - Huang, Edward; Liu, Irene; Lin, James T.
Highlights: A Robust optimization model for flight-to-unloading area assignment problems is developed. A robust plan with constant performance stability can be identified. The model reformulation techniques are applied to speed up the efficiency of the model. The tradeoff between solution robustness and model robustness is studied. A real case study of one of the major airports in Asia is reported. Abstract: One of the major functions of airports is to handle the baggage of customers from check-in counters to aircrafts. To have an efficient baggage handling system (BHS), the assignment of flights on unloading areas must incorporate uncertainties. We develop a robust optimization (RO) model to find a robust plan with constant performance stability in terms of future uncertainty realization. We construct a BHS simulation model to compare different assignment models. The results indicated that the total number of manually handled baggage using the robust plan is 58% lower than that using the current assignment.